Couples Coping With the Serious Illness of One of the Partners - Riazuelo, Hélène (Frontiers in Psychology, 2021)
Chronic kidney failure is a serious somatic disease. Addressing the issue of living with a chronic disease means fully considering the patients’ entourage, their families and those close to them, especially their children and spouses. Objectives: The present paper focuses on the couple’s psychological experience when one of them suffers from a chronic disease, in this instance kidney disease. In particular, how is the spouse affected by the treatment provided? The aim is to see how care for sick people can be improved, but also, more specifically, how relatives and especially partners, can receive attention. Methodology: A qualitative approach is adopted, being based on psychotherapeutic follow-up of the partners of patients with chronic kidney disease, but also of the patients themselves, addressing the matter of their life as a couple. Three couples were considered and two case studies are presented here. The issues that cut across these different situations are examined. Results and Discussion: Some couples show considerable resourcefulness. However, over the years, that capacity for adaptation and inventiveness can also be interrupted by periods of greater suffering and even despair, especially when the somatic pathology becomes chronic. Many spouses talk about how living with a sick partner weighs down on them, causing severe fatigue. Some aspects of the illness can also become traumatic. The disease regularly disrupts the daily life of the couple and the family. This leads to a reworking of family relations. Each couple has its own history with the condition. As it emerges, it can disrupt the bonds of filiation, especially when the illness is hereditary. Making psychological care more accessible to the partners involved constitutes a major challenge for our hospital care systems.